Studi Penafsiran Lafadz Qarin dalam Tafsir Aisar At-Tafasir Karya Abu Bakar Jabir Al-Jazairi - Muhammad Fakih Fiddin; Muhamad Amrulloh; Murdianto Murdianto (Journal of Innovation in Teaching and Instructional Media, 2026)
The concept of qarin in the Qur’an is part of the dynamic relationship between humans and supernatural beings, which has a significant impact on one’s spiritual and moral life. This study aims to analyze the interpretation of the term qarin in Aisar At-Tafasir by Abu Bakar Jabir Al-Jazairi using a thematic (maudhu’i) tafsir approach, as well as to examine its relevance in the lives of contemporary Muslims. This research employs a qualitative method with a library research approach and content analysis. The findings indicate that qarin in the Qur’an carries various meanings depending on the context of the verse: as a misleading companion devil, a bad human friend in the worldly life, or even an angel who records deeds. Aisar At-Tafasir emphasizes that the influence of the qarin, particularly from among the devils, is not absolute and only affects those who turn away from the guidance of the Qur’an. In contrast, believers are accompanied by a righteous qarin who poses no harm. These findings provide important implications for fostering spiritual awareness, self-control, and the development of Islamic character. Theoretically, this study contributes to the development of contemporary thematic tafsir scholarship, particularly in understanding spiritual concepts of the Qur’an through the ijmali approach. Practically, these findings can serve as a foundation for character education and spiritual development of Muslims in the modern era. Thus, a proper understanding of the qarin concept not only strengthens the dimension of faith but also serves as practical guidance in facing spiritual challenges in the modern era.